2001
DOI: 10.1089/152702901750067882
|View full text |Cite
|
Sign up to set email alerts
|

Acute Mountain Sickness; Prophylactic Benefits of Antioxidant Vitamin Supplementation at High Altitude

Abstract: Acute mountain sickness; prophylactic benefits of Free-radical-mediated damage to the blood-brain barrier may be implicated in the pathophysiology of acute mountain sickness (AMS). To indirectly examine this, we conducted a randomized double-blind placebo-controlled trial to assess the potentially prophylactic benefits of enteral antioxidant vitamin supplementation during ascent to high altitude. Eighteen subjects aged 35 +/- 10 years old were randomly assigned double-blind to either an antioxidant (n = 9) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
3
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 21 publications
6
81
3
1
Order By: Relevance
“…There is no doubt that acute exposure to a high altitude will cause pathological stress leading to oxidative stress [34]. Our study showed that the protection of the mitochondria by CO-HBOC also played an important role in the cardiac protective effect.…”
Section: Discussionmentioning
confidence: 58%
“…There is no doubt that acute exposure to a high altitude will cause pathological stress leading to oxidative stress [34]. Our study showed that the protection of the mitochondria by CO-HBOC also played an important role in the cardiac protective effect.…”
Section: Discussionmentioning
confidence: 58%
“…Gingko's effects may be because of its antioxidant activity. This concept is supported by data suggesting that ingestion of antioxidant vitamins may reduce the incidence and severity of AMS [40].…”
Section: Gingko Bilobamentioning
confidence: 77%
“…Taken together, this evidence strongly suggests that combining ALA and VE is better than monotherapy. In parallel, the ALA-VE mixture has been combined with other dietary antioxidants, such as vitamin C, beta-carotene, and selenium, and evaluated under several conditions of exercise, experimental diabetes, cold, age and cancer, and promising results have also been obtained [46][47][48][49][50][51].…”
Section: Synergism Between Lipoate and Tocopherolmentioning
confidence: 99%